Patterns, Determinants and Challenges of Horticulture Diversification in India - Meena, Akshay; Kumar, Ajay; Meena, Anita (Universitas Prasetiya Mulya, 2023)
This study attempts to analyze the trends and patterns of horticulture diversification in India, the differences between states in diversification toward highvalue crops, and identify the factors influencing horticulture diversification. Total horticulture crops have shown moderate diversification. Among horticulture crops, Fruits, plantation crops and spices have exhibited high diversification, whereas high and moderate diversification have been recorded for vegetables during the period under study.The states Assam, Andhra Pradesh, Arunachal Pradesh,Bihar,Gujrat, Kerala, Karnataka, Chhattisgarh, Meghalaya,Madhya Pradesh, Mizoram, Maharashtra, Manipur, Nagaland, Rajasthan, Odisha, Sikkim, Tripura, Telangana, Tamil Nadu,Uttar Pradesh have shown high diversification whereas Jammu & Kashmir, Himachal Pradesh, Haryana, Punjab, Jharkhand, West Bengal, Uttarakhand have displayed moderate diversification in the year 2020-21. Per capita income, annual rainfall, and lagged SID for total horticulture crops all have positive effects on horticulture diversification, whereas fertilizer consumption has a negative effect.